The Therapeutic Role of C-peptide in the Amelioration of Type 1 Diabetes Associated Microvascular Dysfunction of the Kidneys and Nerves: A Systematic Review and Meta-analysis - Champion, Susannah (2012)
Background: There is accumulating evidence indicating that Proinsulin C-peptide is biologically active and exerts a protective physiological role in Type 1 Diabetes Mellitus. Such patients are currently treated with exogenous insulin which lacks C-peptide. This systematic review and meta-analysis aims to establish and evaluate the effect of C-peptide replacement on the renal and nerve function of patients with T1DM and to determine the mechanism by which it may exert its effects. Methods: An electronic search for randomised control trials was carried out in the following databases; Pubmed, EMBASE, Medline, CINAHL, CENTRAL and Proquest. A hand search of key review papers was also completed. In order to ensure that all possible resources were screened for inclusion, the unpublished literature was searched for using SIGLE and www.clinicaltrials.gov. The primary results from included trials were statistically combined in a meta-analysis. Results: Six (6) randomised control trials met the inclusion criteria. Two (2) investigated the effects of C-peptide on kidney function. Three (3) investigated the effects of C-peptide on nerve function. One (1) randomised control trial investigated the effect of C-peptide on both kidney and nerve function. In the included trials, C-peptide was found to exert statistically significant beneficial effects upon urinary albumin excretion, glomerular filtration rate and autonomic and sensory nerve function. When the results from these trials were combined in a meta-analysis, C-peptide was found to exert statistically significant beneficial effects upon albumin excretion and autonomic nerve function when compared to placebo. Conclusion: There is increasing evidence that C-peptide ameliorates the type 1 diabetes associated microvascular dysfunction seen in the kidneys and nerves. The mechanism of C-peptides action appears to be complex and multifaceted and is not fully understood. Evidence from cell systems and experimental models of diabetes xii suggests that C-peptide may influence Na+K+-ATPase and endothelial nitric oxide synthase activity in order to exert its beneficial effects.